(untitled) (Journal of Plant Disease Sciences, 2019)
Morphological variations were observed among the twenty four various isolates of C. gloeosporioides collected from different locations of Vidarbha region of Maharashtra. Based on colony morphology, isolates grouped at Flat and Submerged isolates (7), cottony thick flat and compact (7) and cottony less compact with loose aerial to sub aerial hyphae (10). Conidia of isolate Cg9 recorded maximum broad size (10.50 x 3.7µm) whereas minimum in Cg7 (4.80x 1.78µm), Conidia of Cg11 were narrow in size (7.66 x 1.83µm). Conidia of all other isolates were more or less identical in shape. The average length and breadth of conidia ranged between 4.25 to 10.29 and 1.76 to 3.71µm respectively. The colour of acervuli was light brown to dark in general and the size was maximum in Cg20 (174.34x126.64µm) and minimum in Cg9 (42.59x36.36 µm).